1999
DOI: 10.1128/jb.181.9.2697-2702.1999
|View full text |Cite
|
Sign up to set email alerts
|

The Global Nitrogen Regulator NtcA Regulates Transcription of the Signal Transducer P II (GlnB) and Influences Its Phosphorylation Level in Response to Nitrogen and Carbon Supplies in the Cyanobacterium Synechococcus sp. Strain PCC 7942

Abstract: The PII protein is encoded by a unique glnBgene in Synechococcus sp. strain PCC 7942. Its expression has been analyzed in the wild type and in NtcA-null mutant cells grown under different conditions of nitrogen and carbon supply. RNA-DNA hybridization experiments revealed the presence of one transcript species 680 nucleotides long, whatever the nutrient conditions tested. A second transcript species, 620 nucleotides long, absent in the NtcA null mutant, was observed in wild-type cells that were nitrogen starve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 50 publications
1
25
0
1
Order By: Relevance
“…P‐II is phosphorylated in cyanobacteria and as such interacts with both a phosphatase and a kinase. However, P‐II phosphatase interaction is thought to control nitrate/nitrite assimilation, and as MED4 is unable to grow on those particular nitrogen sources (Moore et al , 2002), and that the kinase activity is reduced when, in the presence of ammonia in another cyanobacterium, Synechococcus elongatus PCC7942 (Lee et al , 1999), this particular function of P‐II may well be redundant within MED4. With regard to amino acid synthesis, P‐II has been shown to increase N ‐acetyl glutamate kinase (NAGK) activity (Maheswaran et al , 2004), an enzyme in the arginine biosynthetic pathway, and identified in Synechococcus (Burillo et al , 2004; Heinrich et al , 2004).…”
Section: Resultsmentioning
confidence: 99%
“…P‐II is phosphorylated in cyanobacteria and as such interacts with both a phosphatase and a kinase. However, P‐II phosphatase interaction is thought to control nitrate/nitrite assimilation, and as MED4 is unable to grow on those particular nitrogen sources (Moore et al , 2002), and that the kinase activity is reduced when, in the presence of ammonia in another cyanobacterium, Synechococcus elongatus PCC7942 (Lee et al , 1999), this particular function of P‐II may well be redundant within MED4. With regard to amino acid synthesis, P‐II has been shown to increase N ‐acetyl glutamate kinase (NAGK) activity (Maheswaran et al , 2004), an enzyme in the arginine biosynthetic pathway, and identified in Synechococcus (Burillo et al , 2004; Heinrich et al , 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence exists for the role of the cellular C-N balance and 2-oxoglutarate levels in sensing the nitrogen status in cyanobacteria (Lee et al 1999, Muro-Pastor et al 2001b). Furthermore, recent findings indicate that 2-oxoglutarate enhances the binding of NtcA to its promoter regions and is required for NtcA-induced transcription (Tanigawa et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This interdependence raised the possibility that PII could play a role as a coordinator between 2‐oxoglutarate production, thence Ci assimilation, and nitrogen metabolism. As a support for this hypothesis, it has been found that growth of Synechococcus PCC 7942 on ammonium as nitrogen source with a high Ci concentration (HC), or in the presence of a low Ci concentration (LC) with nitrate, led to the unphosphorylated form of PII [3,9,10].…”
Section: Introductionmentioning
confidence: 97%